Constructing Indonesian Culinary Heritage through Indomie Packaging: A Multimodal Critical Discourse Analysis - Nurhasanah, Refsi Dewi; Maulana, Ridwan; Aenida, Nadia Alifa Nur; Sajidin, Sajidin; Sulaeman, Dedi (UICELE, 2026)
This study examines how Indonesian identity and everyday nationalism are constructed through the instant noodle packaging of Indomie local culinary variants. The study employs a Multimodal Critical Discourse Analysis (MCDA) method to examine the linguistic and visual components of six different Indomie variants. The focus of the analysis is on the usage of language, local names, food imagery, color schemes, traditional patterns, and depictions of traditional housing and local landmarks. The results indicate that Indomie packaging presents local culinary diversity within the framework of national identity through the term "Kuliner Indonesia" (Indonesian Cuisine) and transforms traditional food into simplified, recognizable, and easily consumable forms. The integration of cohesive linguistic and visual elements subtly and repeatedly mirrors national identity in the everyday consumption habits of people. This research illustrates that instant noodle packaging acts as an important medium for sustaining banal nationalism, where national identity is depicted as something familiar, natural, and taken for granted.